2005
DOI: 10.1081/css-200043367
|View full text |Cite
|
Sign up to set email alerts
|

Copper Content in Agricultural Soils Related to Cropping Systems in Different Regions of Greece

Abstract: Copper (Cu) is naturally present in all soils with a normal range of 2 -60 mg kg 21 . The traditional use of Cu fungicides against mildew diseases has led to the accumulation of Cu in some vineyard and orchard soils. Consequently, there is a move to reduce the use of these compounds in agriculture, especially in organic cultivation. A comprehensive study has not been made of the Cu content of Greek agricultural soils, which are typically alkaline with high clay content and may, therefore, be vulnerable to Cu a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
2
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(28 citation statements)
references
References 13 publications
4
21
2
1
Order By: Relevance
“…In general, differences in the Cu concentrations among vineyards from the same region could be ascribed to variation in soil properties, topography and Cu application history. In the present study and in line with findings by Vavoulidou et al (2005) and Deluisa et al (1996), no significant correlation was found between the analysed soil parameters and the Cu concentrations, probably due to the relatively narrow range of values of the soil properties. Only a weak positive correlation was found between the organic content and the Cu total concentrations (r=0.37, p=0.02) indicative though of Cu-humic complexes as a result of the long history of Cu application and the humification processes.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…In general, differences in the Cu concentrations among vineyards from the same region could be ascribed to variation in soil properties, topography and Cu application history. In the present study and in line with findings by Vavoulidou et al (2005) and Deluisa et al (1996), no significant correlation was found between the analysed soil parameters and the Cu concentrations, probably due to the relatively narrow range of values of the soil properties. Only a weak positive correlation was found between the organic content and the Cu total concentrations (r=0.37, p=0.02) indicative though of Cu-humic complexes as a result of the long history of Cu application and the humification processes.…”
Section: Discussionsupporting
confidence: 80%
“…It was originally developed for the determination of Cu, Zn, Fe and Mn deficiency in neutral and alkaline soils (Lindsay and Norvell, 1978), and is has been frequently adopted for assessing Cu availability in vineyard soils (examples given by Brun et al, 1998;Deluisa et al, 1996 andRomić et al, 2014). The average available Cu concentrations were almost identical for both the surface and deep soil samples (18.7 and 22.6 mg kg -1 , respectively) and were quite similar with the mean value of 15.4 mg kg -1 reported by Vavoulidou et al (2005) for vineyard soils from the same area. The availability ratios that were calculated by dividing the Cu amounts obtained by the DTPA extraction over the total soil content, were almost the same for both the surface soils and the soils collected at 50 cm depth (Fig.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…5 (maximum 20) times and those of Pb 3 (maximum 18) times the precautionary values. Although Cu has an extraordinary high tendency to accumulate in OM (Hiller and Brümmer, 1997), a relation between soil C org and Cu seems to take place only at elevated Cu concentrations > 100-200 mg Cu per kg dry weight (Minnich and McBride, 1986;Vavoulidou et al, 2005;SauvØ, 2006;Fründ et al, 2007). Therefore, the spectral assessment of trace metals may be most feasible at contaminated floodplains aiding in the identification of hot-spot areas and contamination gradients.…”
Section: Interactions and Covariation Between C Org And Trace Metalsmentioning
confidence: 99%
“…Very high concentrations of copper in top vineyard soils have been reported for various world regions due to intensive applications of copper-based fungicide (Prasad et al 1984;Flores-Veles et al 1996;Pietrzak and McPhail 2004;Vavoulidou et al 2005). One of the major problems with copper-polluted soils is the bioavailability of Cu to living organisms.…”
mentioning
confidence: 99%